Pengaruh Gaya Kepemimpinan, Motivasi, Disiplin Kerja, Budaya Organisasi dan Stres Kerja terhadap Kinerja Karyawan PD BKK Brebes - Lutfianah Ulfa; Syariefful Ikhwan; Andi Yulianto; Dwi Harini; Gian Fitralisma (Program Studi Manajemen Universitas Muhadi Setiabudi, 2019)
The purpose of the study was to determine the strength of leadership style, motivaation, discipline, organizational culture, and work stress on the performance of employees of PD BKK (District Credit Bank) Brebes. The population used is PD BKK Brebes employees spread across several branches. Sampling using cluster sampling technique (regional sampling) with a total sample of 52 from 7 office branches. The method of data collection uses questionnaires, interviews and documentation. Data were analyzed using validity tests, reability tests with Alpha Cronbach, multiple linear regression tests with partial test hypothesis testing (t test), simultaneous tests (F test). The results of the analysis in this study showed that simultaneously or together all variables affect employee performance with a calculated F of 33,064 > F of table 2.40 with a probability of 0.000 < of 0.05. For the partial test, the leadership style variable had a positive and significant effect on performance with a calculated value of 2,802 > t table 2.01. The motivation variable had a positive and significant effect on performance with a calculated t value of 2,398 > t table 2,012, the discipline variable had a positive and significant effect on performance with a calculated t value of 3,292 > t table 2,012. The organizational culture variable had a positive and significant effect on employee performance of the calculated t value of 2,554 > t table 2,012. The variable work stress had a negative and insignificant effect on employee performance of the calculated t value of -1,673 < t table 2.012. The conclusion of this study shows that all free variables, namely leadership style, motivation, discipline and organizational culture have a positive effect on employee performance partially and work stress variables do not affect employee performance partially, but all free variables simultaneously affect employee performance.